Clinical and technical challenges of cancer reirradiation: Words of wisdom. (June 2022) - Beddok, Arnaud; Calugaru, Valentin; de Marzi, Ludovic; Graff, Pierre; Dumas, Jean-Luc; Goudjil, Farid; Dendale, Rémi; Minsat, Mathieu; Verrelle, Pierre; Buvat, Irène; Créhange, Gilles
Abstract: Since the development of new radiotherapy techniques that have improved healthy tissue sparing, reirradiation (reRT) has become possible. The selection of patients eligible for reRT is complex given that it can induce severe or even fatal side effects. The first step should therefore be to assess, in the context of multidisciplinary staff meeting, the patient's physical status, the presence of sequelae resulting from the first irradiation and the best treatment option available. ReRT can be performed either curatively or palliatively to treat a cancer-related symptom that is detrimental to the patient's quality of life. The selected techniques for reRT should provide the best protection of healthy tissue. The construction of target volumes and the evaluation of constraints regarding the doses that can be used in this context have not yet been fully codified. These points raised in the literature suggest that randomized studies should be undertaken to answer pending questions. Graphical Abstract: ga1 Highlights: Innovative radiotherapy techniques are placing reirradiation back in the forefront. Patient selection is complex and must be discussed at multidisciplinary meetings. The prevention of radiation-induced injuries remains the priority.